1982
DOI: 10.1021/j100220a017
|View full text |Cite
|
Sign up to set email alerts
|

Electron spin resonance and optical detection of manganese(IV) tetraphenylporphyrin

Abstract: We have demonstrated in this and previous studies that the reactivity of the photoexcited triplet state of porphyrins and chlorophylls with radicals is substantially higher than that of the corresponding ground states. This behavior, not limited to the porphyrin moiety only, was found also with pyrene,1 2345 whose photoexcited triplet exhibits similar chemical reactivity toward transient radicals. The experimental results clearly indicate that PRAP spec-troscopy is most suitable in studying reactions of photoe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1985
1985
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The manganese porphyrin-catalyzed isocyanation reaction mixture (Figure a, red trace) contains similar features and g values (3.91, 2.01) as compared to both the authentic Mn IV (TMP)­(NCO) 2 and the previously reported Mn IV (TPP)­(NCO) 2 , which is consistent with the intermediacy of a Mn IV (TMP)­(NCO) 2 complex during the isocyanation reaction. The spectral features at g = 3.91 and 2.01 are diagnostic of the existence of a high-spin, d 3 Mn IV species with an axially symmetric environment. , Hyperfine splitting of the I = 5/2 55 Mn nucleus of the catalyst is clear at g = 2.01, while the six small features at g = 3.91 can be resolved with derivatives (Figure S3).…”
Section: Resultsmentioning
confidence: 98%
“…The manganese porphyrin-catalyzed isocyanation reaction mixture (Figure a, red trace) contains similar features and g values (3.91, 2.01) as compared to both the authentic Mn IV (TMP)­(NCO) 2 and the previously reported Mn IV (TPP)­(NCO) 2 , which is consistent with the intermediacy of a Mn IV (TMP)­(NCO) 2 complex during the isocyanation reaction. The spectral features at g = 3.91 and 2.01 are diagnostic of the existence of a high-spin, d 3 Mn IV species with an axially symmetric environment. , Hyperfine splitting of the I = 5/2 55 Mn nucleus of the catalyst is clear at g = 2.01, while the six small features at g = 3.91 can be resolved with derivatives (Figure S3).…”
Section: Resultsmentioning
confidence: 98%
“…The six lines shown in Fig. 4c are a typical signal of Mn(IV) species, which indicates the catalytic process should involve high-valent oxo intermediate [42][43].…”
Section: In Situ Epr Spectra Study Of Cyclohexene Epoxidationmentioning
confidence: 97%
“…Before this work, the roles of TPPMnCl and isobutyraldehyde have been well studied. As the literature reported, , it was suggested that the manganese porphyrin reacted with the aldehyde to generate an acyl radical at first, which was oxidized by O 2 generating acylperoxy radicals. Then the acylperoxy radical could act as a carrier by reacting with another aldehyde to give peroxyacid, thereby generating another acyl radical.…”
Section: Resultsmentioning
confidence: 98%